PENGARUH PENGAJARAN INDIVIDUAL TERHADAP PENGEMBANGAN KREATIVITAS SISWA DALAM FISIKA - Mastuan Mastuan (Universitas Lambung Mangkurat, 2010)
Abstract: This research intended to study the effect of individual instruction to the development of student creativity in physics. Different from classical instruction in which teachers assume that all students have the same ability, maturity and the same rate of learning, on individual instruction it is considered that students have their own ability, intelegence, talent, personality, and achievement. This study used “post test only control group” design.. From the statistical calculation it was found that t '= 8.43 while t tabel = 2.02 with the real level = 0.05 Since t' does not lie between +2.02 and -2.02 then H0 was rejected so that H1 was accepted. It can be concluded that there were significant differences in creativity scores of the first grade students in 3’s Junior High School Makassar, between students who are taught by classical instruction and students who are taught by individual instructionKey words: individual instruction, creativity in physics